Kinerja Reproduksi dan Potensi Pengembangan Kerbau Gayo di Kabupaten Aceh Tengah - Alkautsar Alkautsar; Komariah Komariah; Rudy Priyanto (Faculty of Agriculture, Musamus University, 2022)
This study aimed to analyze the productivity of gayo buffalo at different body colors comprehensively based on reproduction performance, to analyze the population structure of gayo buffalo, and evaluate the potential development of gayo buffalo based on the availability of forage in approach of study to KPPR Value (the capacity of ruminants population increasing) in Central Aceh District, Aceh Province.This research method used were the survey and direct observation (interview with the structured questionnaire). This research used the primary data was 250 buffalo or 65 farmers as respondent, and the secoundary data used to analyze the reproduction performance of gayo buffalo which was different body color, also used to analyze the potential development strategy of gayo buffalo. the productivity performance of gayo buffalo were analyzed from BCS (Body ondition Scoring) value to estimate body weight of gayo buffalo. The result showed that the reproduction performance closed to perfect, except the value of calving interval. The average of BCS value of the different gayo buffalo’s body color was found as <3, which the BCS value of female gayo buffalo was smaller than male, at the older ages. The result showed that the body weight of the female gayo buffalo in the different body color was higher balue than male, at the older group of ages. The result showed that the KPPTR value of Bintang Regency was 5,295,66 ST, slightly higher than KPPTR value of Linge Regency which was 5,212,99 ST